2018
DOI: 10.3390/rs10121950
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Trade-off Between Spatial and Temporal Resolution of a Geosynchronous SAR Mission for Soil Moisture Monitoring

Abstract: The next generation of synthetic aperture radar (SAR) systems could foresee satellite missions based on a geosynchronous orbit (GEO SAR). These systems are able to provide radar images with an unprecedented combination of spatial (≤1 km) and temporal (≤12 h) resolutions. This paper investigates the GEO SAR potentialities for soil moisture (SM) mapping finalized to hydrological applications, and defines the best compromise, in terms of image spatio-temporal resolution, for SM monitoring. A synthetic soil moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…In fact, the MCSs which form over land (e.g., in the Sahel where they are responsible for the majority of annual rainfall [94]) are known to be controlled by the surface properties [95]. The added value of the Hydroterra soil moisture observation in the hydrological framework have been discussed in [29]. Future works are needed to assess the impact of these new observations (ZTD and soil moisture) in a complete hydro-meteorological framework that is very important to forecast high impact weather events over areas with complex terrain, such as the Mediterranean region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the MCSs which form over land (e.g., in the Sahel where they are responsible for the majority of annual rainfall [94]) are known to be controlled by the surface properties [95]. The added value of the Hydroterra soil moisture observation in the hydrological framework have been discussed in [29]. Future works are needed to assess the impact of these new observations (ZTD and soil moisture) in a complete hydro-meteorological framework that is very important to forecast high impact weather events over areas with complex terrain, such as the Mediterranean region.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning soil moisture, the added value of Hydroterra-derived estimates has been discussed in Cenci et al [29]. To the best of our knowledge, a similar kind of analysis has never been carried out for ZTD estimates from Hydroterra observations and their impacts on the predictive capability of severe hydro-meteorological events.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to SMC levels, a variety of other factors contribute to the backscattered radar signal, from surface characteristics like the surface roughness profile, the mineralogical composition of the soil, and the dielectric features of the soil to radar characteristics like the incidence angle (from nadir), the operating frequency of the radar sensor, and polarisation [ 24 ]. Moreover, the soil dielectric features or dielectric constant ( εs ) exhibit a polynomial relationship with SMC, and other dependencies have been found between SMC and the mineralogical composition of soil and SAR frequency [ 18 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the authors of [ 16 , 17 ] proposed semi-empirical calibrations of RMS height and correlation length to improve the characterisation of surface roughness parameters, which produced better results. The revisit time of high-resolution SARs is still inadequate, which makes tracking SMC temporal variations difficult [ 18 ]. Susceptibility to medium-to-thick vegetation cover, which consequently causes volume scattering, has a direct and negative impact on the accuracy of SMC retrieval [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cenci et al [14] compared a SAR in geostationary orbit to a more traditional SAR in polar orbit, in terms of spatial and temporal resolution, by means of data assimilation into hydrological models. They found that a geostationary SAR can be a valuable contribution to hydrological applications if the spatial resolution is kept high (∼100 m).…”
Section: On the Interest Of New Observing Systemsmentioning
confidence: 99%